Pengujian Struktur Mikro dan Mekanik pada Pipa Ketel Uap Sebelum dan Sesudah Pemakaian Selama 10 Tahun - Habibi Santoso (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
This journal aims to determine the quality and nature of the weldability of boiler pipes are still good and after use for 10 years. As a reference temporary repairs to a pipe leaking boiler. Steps to be done is to compare the test results of mechanical properties and microstructure of both types of the pipe. The parameters used are hardness, tensile strength and microstructure of both types of pipe. The test results on the pipe that is good value average hardness of 148 HV, while the broken pipe an average hardness value of 118 HV a decline of 30 HV. Tensile tests on pipes that are good value tensile strength of 50 kg / mm2 (490 MPa), the broken pipe grades tensile strength of 40 kg / mm (392 MPa), a decline of 10 kg / mm (98 MPa). The test results are good pipe microstructure consisting of ferrite and pearlite structure while at the broken pipe consisting of ferrite phase. In accordance with the results of hardness testing in which the phase of ferrite and pearlite harder than the ferrite phase. The final conclusion is that the pipeline after use for 10 years has decreased mechanical properties, namely: hardness and tensile strength. This is a result of the depletion of the wall thickness due to corrosion